The price and trade effects of strict information requirements for genetically modified commodities: Under the Cartagena Protocol on Biosafety - Bouët, Antoine; Gruère, Guillaume P.; Leroy, Laetitia (International Food Policy Research Institute, 2011)
This paper assesses the global economic implications of the proposed strict documentation requirements on traded shipments of potentially genetically modified (GM) commodities under the Cartagena Protocol on Biosafety. More specifically, we evaluate the trade diversion, price, and welfare effects of requiring all shipments to bear a list of specific GM events (the does contain rule) in the maize and soybean sectors. Using a spatial equilibrium model with 80 maize- and 53 soybean-trading countries, we show that information requirements would have a significant effect on the world market for maize and soybeans. But they would have even greater effects on trade, creating significant trade distortion that diverts exports from their original destination. The measure would also lead to significant negative welfare effects for all members of the Protocol and nonmembers that produce GM maize, soybeans, or both. While non-GM producers in Protocol member countries would benefit from this regulation, consumers and producers in many developing countries would have to pay a proportionally much heftier price for such a measure.